OLAP Techniques for Approximation and Mining Query Answering - Murtadaha Hamd; Waleed Hassan (Al-Rafidain Journal of Computer Sciences and Mathematics)
Data warehouse (DW) systems have become a key component of the corporate information system architecture, in which they play a crucial role in building business decision support systems by collecting and consolidating data from a variety of internal and external sources. The content of a DW is analyzed by the On-Line Analytical Processing (OLAP) applications for the purpose of discovering trends, patterns of behavior, and anomalies as well as finding hidden dependencies between data . Through this research, theoretical concepts which are related with OLAP and Data Warehouse are studied in detail. In this work the SALES Data Warehouse  (SALESDW) , procedures are implemented and algorithms are developed like ODBC (Open DataBase Connectivity) for different sources, and Data cleansing to carry out the consistency of Data Warehouse (DW). The aim of the research are design a prototype of a SALES Data Warehouse (SALESDW) by adding and implementing the essential concepts , and implementing the OLAP techniques ( tools) on SALESDW.